Identifikasi Sebaran Batugamping Menggunakan Data Citra Landsat 8 Di Pulau Buton Bagian Selatan (Jurnal Geomine, 2022)
Indonesia has a large potential for industrial minerals and is spread in almost all parts of Indonesia. Buton Island, which is located in one of the southeastern arms of Sulawesi, is one of Indonesia's regions that has a large potential for limestone, the reef limestone has undergone a geological process until it was lifted 700 m to the surface. This study was to identify how the distribution of limestone using Landsat 8 OLI image data. This research was conducted by processing Landsat 8 image data and then analyzing and carrying out several interpretation methods so that the distribution of limestones can be well. The interpretation method used in Landsat 8 imagery is the RGB (Red Green Blue) composite band method, band ratio, and band spectrum. In Landsat 8 imagery data, the interpretation method used is to obtain two classifications of limestone distribution, namely the distribution of high potential limestone and low potential limestone distribution. After processing Landsat 8 image data, this study also carried out direct checks in the study area to support the success of the results carried out. This research is large enough to utilize Landsat 8 imagery data for further exploration.